1989
DOI: 10.1016/0022-4375(89)90008-x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting automobile safety belt use by young children

Abstract: A program using behavioral practice, assertiveness training, and social and contrived reinforcers was developed to establish and maintain automobile safety belt use by young children. Sixteen children (ages 4.8 to 7 years) who never used their safety belts during a 5-day preexperimental observation period were randomly assigned to two groups of eight each. A multiple baseline design across groups was used to evaluate the effectiveness of the training program. During the 8-day baseline period for Group 1, no ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This finding replicates those of previous studies~Lehman & Geller, 1990;Sowers-Hoag et al, 1987! and extends them to a Mediterranean culture. By including steps meant to increase awareness in the pre-intervention stages, our findings also suggest that behavioral changes in parents did not stem from awareness alone.…”
Section: Discussionsupporting
confidence: 94%
“…This finding replicates those of previous studies~Lehman & Geller, 1990;Sowers-Hoag et al, 1987! and extends them to a Mediterranean culture. By including steps meant to increase awareness in the pre-intervention stages, our findings also suggest that behavioral changes in parents did not stem from awareness alone.…”
Section: Discussionsupporting
confidence: 94%
“…These intervention effects were achieved without the use of extrinsic rewards, and the gains were similar to increases in safety belt use following incentive/reward programs for adults (see reviews by Geller, 1984Geller, , 1988Geller, Rudd, Kalsher, Streff, & Lehman, 1987) and for children (Roberts & Fanurik, 1986;Roberts & Layfield, 1987). Sowers-Hoag et al (1987) showed greater gains in safety belt use with their intervention package, which induded education, assertiveness training, behavioral rehearsal, and a prize lottery. However, these investigators only examined the program impact for children (n = 16) who never used a safety belt during a "five-day pre-experimental observation period" (p. 134).…”
Section: Shoulder Belt Usementioning
confidence: 86%
“…For example, Roberts and Turner (1986) rewarded parents with lottery tickets redeemable for prizes if their children were buckled up when arriving at 219 1990,23,[219][220][221][222][223][224][225] NUMBEP, 2 (summER 1990) day-care centers; Roberts and Layfield (1987) directly rewarded preschool children with colorfu stickers when they were buckled up correctly upon arrival at day-care centers; Roberts and Fanurik (1986) and Roberts, Fanurik, and Wilson (1988) taught PTA volunteers to reward elementary school children with lapel stickers, lottery tickets for pizzas, bumper stickers, and coloring books if all vehide occupants were buckled up when arriving at school; and Sowers-Hoag, Thyer, and Bailey (1987) The parents of the kindergarten children were invited to come early one afternoon (i.e., 2:30 p.m. instead of 3:00 p.m.), and watch the "Buckie Buckle Show." On the next day, the kindergarten children performed the "Buckie Buckle Show" during school hours for the children in the primary classes.…”
mentioning
confidence: 99%
“…Besides preventing possible injury or death, these interventions can also head off the emotional harm that is a frequent aftermath of these traumatic events. Some self protective skills that have been taught are automobile safety belt usage to youth (Sowers Haag, Thyer, & Bailey, 1987;M. Williams, Thyer, Bailey, & Harrison, 1989), safe responses when finding a gun in a house (M. B. Himle, Miltenberger, Flessner, & Gatheridge, 2004;Miltenberger et aI., 2005), skills for young children to avoid abduction (Johnson et aI., 2005(Johnson et aI., , 2006Miltenberger & Thiesse-Duffy, 1988), steps for identifying and treating children's illnesses for parents at risk of child abuse and neglect (Bigelow & Lutzker, 2000), ways to reduce home safety hazards for parents reported for child neglect (Metchikian, Mink, Bigelow, Lutzker, & Doctor, 1999), and self-preservation and emergency responses for battered families (Lund & Greene, 2003).…”
Section: Safety and Preventionmentioning
confidence: 99%